Evaluation of bran extracts of rice (Oryza sativa) and selected bean (Phaseolus vulgaris L.) varieties for their antioxidative and anti-hyperglycemic potentials - Marikkar, J.M.N.; Nuurhaffiszzulullah, A.A.; Gunarathne, K.M.R.U. (University of Jaffna, 2021)
Search of therapeutic potential of natural and locally available food has become a trend due to increasing health concerns among consumers around the world. In this study, extracts of rice bran (Oryza sativa L.) and selected beans (red bean, red kidney bean, and white bean) (Phaseolus vulgaris L.) were obtained using 80% ethanol-water mixture to compare their anti-hyperglycaemic and anti-oxidative potentials. The total phenolic content (TPC), ferric reducing antioxidant power (FRAP), 2,2’-azino bis (3-ethylbenzothiazoline-6- sulfonic acid (ABTS) radical scavenging activity, 2,2-diphenyl-1-picryl-hydrazylhydrate (DPPH) radical scavenging activity, and the carbohydrate hydrolyzing enzyme inhibitory potentials of the extracts were studied in-vitro using relevant assays. The highest phenolic content (0.122 mg of Gallic Acid Equivalent /g of extract) was found with red bean extract. FRAP values of the extracts were found to range from 48.98 to 75.94 µmol FeSO4 /g bran extract. The highest ferric reducing power (75.94 µmol FeSO4 /g) was displayed by the bran extract of red kidney bean. The highest inhibitory effect against α-amylase (96.18%) was displayed by rice bran extract and the highest inhibitory effect against α-glucosidase (39.57%) was exhibited by red bean extract. This study concluded that the bran extracts of rice and the selected beans were potent sources of natural antioxidants and good postprandial hyperglycaemia regulators.
Keywords: Antioxidant activity; Antihyperglycemic activity; Rice bran; Diabetes